2014
DOI: 10.1111/mcn.12123
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of preterm birth and intrauterine growth restriction to childhood undernutrition in Tanzania

Abstract: Objectives were to examine the growth patterns of preterm and growth‐restricted infants and to evaluate the associations of prematurity and intrauterine growth restriction (IUGR) with risk of stunting, wasting and underweight. Data from a cohort of HIV‐negative pregnant women–infant pairs were collected prospectively in Tanzania. Small for gestational age [SGA, birthweight (BW) <10th percentile] was used as proxy for IUGR. Anthropometry was measured monthly until 18 months. Length‐for‐age (LAZ), weight‐for‐len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
0
17
0
2
Order By: Relevance
“…Poor post-natal growth (weight, length or head circumference) is primarily due to inadequate nutritional intake [6]. This early growth deficit affects brain development and has been shown to result in poorer neurodevelopmental outcomes later in life [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor post-natal growth (weight, length or head circumference) is primarily due to inadequate nutritional intake [6]. This early growth deficit affects brain development and has been shown to result in poorer neurodevelopmental outcomes later in life [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Early growth deficits amongst preterm infants results from protein and energy deficits after birth [6] and are associated with poor growth and neurodevelopmental outcomes later in childhood [7,8]. Even with growing evidence that optimizing nutrition with total parenteral nutrition, early enteral feeds with fast advancement and fortification of human milk improves growth outcomes, resource limited settings have not been able to implement all this because of cost.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that both physical and social factors are responsible for chronic undernutrition among children [7,8]. Stunting often begins in the pre-natal phase and continues to two years (a time period called the '1,000 days') after the birth of a child [9][10][11][12][13]. Furthermore, the volume, frequency and nature of supplementary feeding, birth weight, gender, birth order and disease conditions are all linked with stunting among children [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Stunting often begins in utero , as maternal nutrition is the first determinant of the child nutritional status [ 1 , 10 ], and continues generally during the first two years after birth [ 11 , 12 ]. Although the pathogenesis of stunting is not yet well-understood, studies have shown that inadequate nutrient intake, infections, unsafe water and poor child care are among its main determinants [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%